2002
DOI: 10.4049/jimmunol.168.7.3543
|View full text |Cite
|
Sign up to set email alerts
|

Gq Signaling Is Required for Allergen-Induced Pulmonary Eosinophilia

Abstract: The complexity and magnitude of interactions leading to the selective infiltration of eosinophils in response to inhaled allergens are formidable obstacles to a larger understanding of the pulmonary pathology associated with allergic asthma. This study uses knockout mice to demonstrate a novel function for the heterotrimeric G protein, Gq, in the regulation of pulmonary eosinophil recruitment. In the absence of Gq signaling, eosinophils failed to accumulate in the lungs following allergen challenge. These stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…To exmine the role of Gαq in immune responses in a primary T‐cell model we used the Gαq −/− mouse. Previous studies of Gαq −/− mice had shown that they had normal haematopoiesis and no difference in IL‐4 and INF‐γ secretion from activated T cells 28, 31. Interestingly, T cells isolated from the spleens of Gαq −/− mice secreted two‐ to threefold more IL‐2, IL‐5, IL‐12 and TNF‐α than T cells from WT mice following stimulation with anti‐CD3/anti‐CD28 beads (mean±SEM; n =4, p <0.05), but displayed no significant difference in levels of secreted IL‐4 and INF‐γ although these cytokines also tended to increase (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To exmine the role of Gαq in immune responses in a primary T‐cell model we used the Gαq −/− mouse. Previous studies of Gαq −/− mice had shown that they had normal haematopoiesis and no difference in IL‐4 and INF‐γ secretion from activated T cells 28, 31. Interestingly, T cells isolated from the spleens of Gαq −/− mice secreted two‐ to threefold more IL‐2, IL‐5, IL‐12 and TNF‐α than T cells from WT mice following stimulation with anti‐CD3/anti‐CD28 beads (mean±SEM; n =4, p <0.05), but displayed no significant difference in levels of secreted IL‐4 and INF‐γ although these cytokines also tended to increase (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Gαq −/− mice and Gα11 −/− mice were bred as described previously 31, 48 in the animal house of the University of Heidelberg with permission to Stefan Offermans/Nina Wettschureck from the local authorities (Regierungspräsidium Karlsruhe). CD3 + T cells were isolated from cell suspensions of ground mouse spleens by negative selection using Dynal Mouse T Cell Negative Isolation Kit.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are several reasons that can explain the apparent discrepancy between the older studies and the current study. First, given the critical importance of Gi in both the classical and alternative chemokine receptor signaling pathways, it is not possible to visualize the alternative signaling pathway unless Gα q is selectively targeted in a Gα i2 -sufficient cell and, to our knowledge, only a single study examining Gα q -deficient leukocytes has been published ( 63 ). Second, many of the previous biochemical studies analyzed signaling through CXCR1/CXCR2, the receptors for IL-8 and Mip2 ( 5 7 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils were isolated from the spleens of naïve IL-5-TG mice, following the method previously described for isolating them from blood (2). In brief, single-cell suspensions of spleens were layered onto a Percoll gradient (60% Percoll [ ϭ 1.084] 1ϫ Hanks balanced salt solution, 15 mM HEPES [pH 7.4], and 0.003 N HCl) and centrifuged (45 min, 1,200 ϫ g, 4°C).…”
Section: Methodsmentioning
confidence: 99%